2019
DOI: 10.1002/aocs.12194
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Extension Validation of AOCS Ce 2c‐11 for Omega‐3 Polyunsaturated Fatty Acids in Conventional Foods and Dietary Supplements Containing Added Marine Oil

Abstract: Marine oils are commonly added to conventional foods and dietary supplements to enhance their contents of omega-3 polyunsaturated fatty acids (PUFA), including eicosapentaenoic acid (EPA; 20:5n-3) and docosahexaenoic acid (DHA; 22:6n-3), which have been associated with numerous potential health benefits. This study compared American Oil Chemists' Society (AOCS) Official Methods Ce 2b-11 and Ce 2c-11 for determining EPA and DHA in foods and dietary supplements and found that AOCS Ce 2c-11 produces significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Figure 1 shows the different profiles of FA obtained by GC-FID for a natural FO supplement (Figure 1-A, Sample 1) and a concentrated FO supplement (Figure 1-B, Sample 10). It can be observed that the natural FO presented a large number of major peaks besides EPA and DHA, with a high amount of saturated fatty acids (SFA), such as C14:0 and C16:0, monounsaturated fatty acids (MUFA), such as C16:1 and C18:1, and some characteristics PUFA, such as C16:2, C16:3, C16:4, C18:4, C21:5, and C22:5 also reported by other researchers [11,12]. Several isomers were also separated in this natural FO (C16:1, C18:1, C18:2, C18:3, 20:4, and 22:5).…”
Section: Fatty Acid Composition and Form Of Natural And Concentrated Fish Oil Supplementssupporting
confidence: 71%
“…Figure 1 shows the different profiles of FA obtained by GC-FID for a natural FO supplement (Figure 1-A, Sample 1) and a concentrated FO supplement (Figure 1-B, Sample 10). It can be observed that the natural FO presented a large number of major peaks besides EPA and DHA, with a high amount of saturated fatty acids (SFA), such as C14:0 and C16:0, monounsaturated fatty acids (MUFA), such as C16:1 and C18:1, and some characteristics PUFA, such as C16:2, C16:3, C16:4, C18:4, C21:5, and C22:5 also reported by other researchers [11,12]. Several isomers were also separated in this natural FO (C16:1, C18:1, C18:2, C18:3, 20:4, and 22:5).…”
Section: Fatty Acid Composition and Form Of Natural And Concentrated Fish Oil Supplementssupporting
confidence: 71%
“…The fatty acid profiles of KO emulsions, with a specific focus on changes in EPA and DHA during accelerated storage, were determined using GC-MS (Agilent, America). This process involved the removal of unsaponifiable matter, extraction of saponifiable matter with hexane, and analysis under controlled conditions, including temperature gradients and injection volume, following the method described by Li et al (2019).…”
Section: Dha and Epa Analysismentioning
confidence: 99%
“…SRM 3275 has found wide use to validate methods and serve as a QC material as demonstrated by Srigley and coworkers ( 86 89 ) at the FDA reporting several studies using SRM 3275 for validation of methods. In a study to evaluate the overall fatty acid composition of 46 marine oil omega-3 supplements, Srigley and Rader analyzed SRM 3275 (all three levels) using GC-FID on a novel ionic liquid phase column ( 90 ).…”
Section: Case Studies Of Research Using Dietary Supplement Matrix Crmsmentioning
confidence: 99%